Genomic clone for sandbar shark lambda light chain: generation of diversity in the absence of gene rearrangement. - Hohman, V S (1993)
While the general structure of immunoglobulin chains has remained relatively unchanged throughout evolution, the organization of the genes encoding these molecules differs substantially. To understand how the rearranging immunoglobulin system arose, it is necessary to examine living representatives of the most early vertebrate phyla. Elasmo-branches, which include the sharks, skates, and rays, are the most primitive phylogenetic class of vertebrates from which immunoglobulin DNA sequences have been obtained. In the sandbar shark (Carcharhinus plumbeus), the genes are arranged in individual clusters in which a single variable (V), joining (J), and constant (C) region gene, along with upstream regulatory elements, span a distance of approximately 4.4 kb or approximately 5.8 kb. We report the complete sequence of a genomic clone encoding sandbar shark lambda light chain. A unique finding of our study is that the V and J genes are fused in the germ line. Three additional clones have been shown by DNA sequencing to also have fused V and J genes. The four clones have complementarity-determining regions 3 of various lengths and amino acid sequence variability similar to the products of rearranged genes. Furthermore, analysis by polymerase chain reaction technology revealed an additional 26 genomic clones demonstrating fusion of the V and J segments. Therefore, VJ fusion is the prominent organizational feature of sandbar shark immunoglobulin light chain genes. This finding raises questions concerning the necessity of recombination to produce an antibody repertoire capable of reacting against a diverse array of antigens.